High‐resolution bathymetry reveals contrasting landslide activity shaping the walls of the Mid‐Atlantic Ridge axial valley. (24th April 2013) - Cannat, Mathilde; Mangeney, Anne; Ondréas, Hélène; Fouquet, Yves; Normand, Alain
Abstract: [1] Axial valleys are found along most slow‐spreading mid‐ocean ridges and are one of the most prominent topographic features on Earth. In this paper, we present the first deep‐tow swath bathymetry for the axial valley walls of the Mid‐Atlantic Ridge. These data allow us to analyze axial valley wall morphology with a very high resolution (0.5 to 1 m compared to ≥ 50 m for shipboard multibeam bathymetry), revealing the role played by landslides. Slow‐spreading ridge axial valleys also commonly expose mantle‐derived serpentinized peridotites in the footwalls of large offset normal faults (detachments). In our map of the Ashadze area (lat. 13°N), ultramafic outcrops have an average slope of 18° and behave as sliding deformable rock masses, with little fragmentation. By contrast, the basaltic seafloor in the Krasnov area (lat. 16°38′N) has an average slope of 32° and the erosion of the steep basaltic rock faces leads to extensive fragmentation, forming debris with morphologies consistent with noncohesive granular flow. Comparison with laboratory experiments suggests that the repose angle for this basaltic debris is > 25°. We discuss the interplay between the normal faults that bound the axial valley and the observed mass wasting processes. We propose that, along axial valley walls where serpentinized peridotites are exposed by detachment faults, mass wasting results in average slopes ≤ 20°, even in places where the emergence angle of the detachment is larger. Key points: Landslides shape slopes of axial valley at the Mid‐Atlantic Ridge Mass‐wasting is different in serpentinized peridotite and in basalts Landslides limit overall slopes of ultramafic outcrops to about 20 degrees